Association mapping and domestication analysis to dissect genetic improvement process of upland cotton yield-related traits in China - Chunping GUO; Zhenyuan PAN; Chunyuan YOU; Xiaofeng ZHOU; Cong HUANG; Chao SHEN; Ruihai ZHAO; Qingyong YANG; Longfu ZHU; Raheel SHAHZAD; Fande MENG; Zhongxu LIN; et al. (Journal of Cotton Research, 2021)
Abstract Background Cotton fiber yield is a complex trait, which can be influenced by multiple agronomic traits. Unravelling the genetic basis of cotton fiber yield-related traits contributes to genetic improvement of cotton. Results In this study, 503 upland cotton varieties covering the four breeding stages (BS1–BS4, 1911–2011) in China were used for association mapping and domestication analysis. One hundred and forty SSR markers significantly associated with ten fiber yield-related traits were identified, among which, 29 markers showed an increasing trend contribution to cotton yield-related traits from BS1 to BS4, and 26 markers showed decreased trend effect. Four favorable alleles of 9 major loci (R 2 ≥ 3) were strongly selected during the breeding stages, and the candidate genes of the four strongly selected alleles were predicated according to the gene function annotation and tissue expression data. Conclusions The study not only uncovers the genetic basis of 10 cotton yield-related traits but also provides genetic evidence for cotton improvement during the cotton breeding process in China.